Administration of probiotics to increase egg production and extend the productivity on late-phase laying hen: a review - Kumalasari, Chitra; Adriani, Lovita; Yudha Asmara, Indrawati; Nayan, Nazri (ResearchersLinks, 2023)
Eggs are a relatively inexpensive and easily obtained food. The average laying hens produce 240 – 260 eggs/bird/year. However, at the age of 80 weeks laying hens must be culled because their productivity has decreased below50%. Many efforts have been made to extend the egg production cycle so that production increases before laying hensare culled. Probiotics supplementation is one method of increasing productivity in old age laying hens. This reviewexplores the potential of probiotics that can increase egg production in laying hen late-phase, which discusses the reproductivesystem, including hormones and the reproductive tract, productivity, digestive system, and health of layinghens at an advanced age. This article attempts to provide a complete summary of the potential benefits of probiotics inprolonging the production cycle of late-phase laying hens based on existing literature. The research presented in thisstudy offers pertinent insights and theoretical frameworks for enhancing productivity in aging hens, particularly for individuals engaged in small-scale farming.